MODERN VIEW IN THE TREATMENT OF PATIENTS WITH TYPE 2 DIABETES MELLITUS - Sodikov , Samad Salahiddinovich; Eshimov , Zafariddin; Ergashev, Nurjaxon; Muxammadiyev, Temur (Educational Research in Universal Sciences, 2024)
The incidence of type 2 diabetes mellitus (T2DM) is very high and continues to grow alarmingly, being the leading cause of mortality in the population. The medical and social significance of T2DM is determined primarily by its severe vascular and neurological complications, which lead to early disability and high mortality, reduced life expectancy and deterioration in its quality. T2DM is characterized by progressive dysfunction of pancreatic β-cells accompanied by the development of insulin resistance. The article discusses the mechanisms of action of hypoglycemic drugs from the group of peroxisome proliferator-activated receptor (PPARγ) agonists - pioglitazone and the group of dipeptidyl peptidase-4 inhibitors - alogliptin. Pioglitazone improves insulin sensitivity through increasing the expression of numerous genes encoding proteins or proteins that modulate glucose and fat metabolism. Alogliptin increases glucose-dependent activity of β-cells with a low risk of hypoglycemia, suppresses increased secretion of glucagon, and has cardiovascular safety. The feasibility of using a fixed combination of pioglitazone and alogliptin has been substantiated, which makes it possible to effectively and safely manage T2DM, simultaneously influencing 10 of 11 pathophysiological disorders that lead to the development of the disease.